Toll‐like Receptor 4 Signaling in Neurons Enhances Calcium‐Permeable α‐Amino‐3‐Hydroxy‐5‐Methyl‐4‐Isoxazolepropionic Acid Receptor Currents and Drives Post‐Traumatic Epileptogenesis. Issue 4 (24th February 2020) - Korgaonkar, Akshata A.; Li, Ying; Sekhar, Dipika; Subramanian, Deepak; Guevarra, Jenieve; Swietek, Bogumila; Pallottie, Alexandra; Singh, Sukwinder; Kella, Kruthi; Elkabes, Stella; Santhakumar, Vijayalakshmi
Abstract : Objective: Traumatic brain injury is a major risk factor for acquired epilepsies, and understanding the mechanisms underlying the early pathophysiology could yield viable therapeutic targets. Growing evidence indicates a role for inflammatory signaling in modifying neuronal excitability and promoting epileptogenesis. Here we examined the effect of innate immune receptor Toll‐like receptor 4 (TLR4) on excitability of the hippocampal dentate gyrus and epileptogenesis after brain injury. Methods: Slice and in vivo electrophysiology and Western blots were conducted in rats subject to fluid percussion brain injury or sham injury. Results: The studies identify that TLR4 signaling in neurons augments dentate granule cell calcium‐permeable α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor (CP‐AMPAR) currents after brain injury. Blocking TLR4 signaling in vivo shortly after brain injury reduced dentate network excitability and seizure susceptibility. When blocking of TLR4 signaling after injury was delayed, however, this treatment failed to reduce postinjury seizure susceptibility. Furthermore, TLR4 signal blocking was less efficacious in limiting seizure susceptibility when AMPAR currents, downstream targets of TLR4 signaling, were transiently enhanced. Paradoxically, blocking TLR4 signaling augmented both network excitability and seizure susceptibility in uninjured controls. Despite the differential effect on seizure susceptibility, TLR4 antagonism suppressed cellular inflammatory responses after injury without impacting sham controls. Interpretation: These findings demonstrate that independently of glia, the immune receptor TLR4 directly regulates post‐traumatic neuronal excitability. Moreover, the TLR4‐dependent early increase in dentate excitability is causally associated with epileptogenesis. Identification and selective targeting of the mechanisms underlying the aberrant TLR4‐mediated increase in CP‐AMPAR signaling after injury may prevent epileptogenesis after brain trauma. ANN NEUROL 2020;87:497–515 Abstract : Summary of interactions between Toll‐like receptor 4 (TLR4) signaling and brain injury on network excitability and epileptogenesis. Graphic illustration of the effect of injury and early TLR4 antagonist treatment on early network excitability and the long‐term network state. The schematic neurons include TLR4 and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor (AMPAR) subunit expression profiles in the acute phase of sham or brain injury. The corresponding early effects on network excitability are depicted by schematic population response traces (inset on upper left). Note the increase in excitability of the uninjured neuron after TLR4 antagonism without changes in AMPAR expression. Note also the increase in TLR4, calcium permeable AMPARs, and population excitability after injury and its reduction by TLR4 antagonist treatment. Ampakine enhancement of excitability during TLR4 antagonism is illustrated. The early phase responses and manipulations (including injury, treatments, and molecular responses) are superimposed on a 2‐tone color‐coded network state topology, where green indicates low‐normal network excitability, ensuring network stability and low risk for epilepsy (inset on upper right). Note the correspondence between early excitability state (population response profile) and long‐term seizure susceptibility and the effects of pharmacological manipulations.